Temprature Effect on Photovoltaic Parameters for c-Si and a-Si Solar Cells - F. F. Kahzahl (Iraqi Journal for Electrical and Electronic Engineering, 2007)
Although solar cell parameters are generally measured at 20-30 Co, flat platemodules normally operate at 40-50 Co under terrestrial conditions and even highertemperatures are used for some concentrator cell applications. Therefore it isinteresting to calculate the dependence of cell parameters on temperature. In this papera simple formulation has been derived for obtaining the temperature dependence ofopen circuit voltage Voc, short circuit current density Jsc, fill factor FF, andconversation efficiency η, for c-Si and a-Si solar cells.